A study on students' satisfaction over academic services provided by Kuantan Community College / Nurul Nazati Nazahar - Nazahar, Nurul Nazati (2013)
Students of any private or public higher learning institutions can be regarded as customers to these organizations. Thus, it is very important to take care of their satisfaction in ensuring the best service and a quality education are delivered to them. Student satisfaction can improve the image of that education institution as well as attracting more students to enroll at that education institution. Community College is one of the Public Higher Learning Institution which responsible in providing good education to youth in helping them developing a better life in the future. This study will be carried out at Kuantan Community College in Pahang which only offering certificate courses for their students. Other than that, this study will focus on students' satisfaction over academic services quality provided by the Kuantan Community College. The students' satisfaction will be measured based on SERVQUAL five dimensions developed by Parasuraman et al. The five dimensions are tangible, reliability, responsiveness, assurance, and empathy. The sampling technique used in getting the sample size was proportionate stratified random sampling. Based on the result students in Kuantan Community College satisfied with academic services provided by the college.